Hybrid simulation modelling of the human-production process interface in lean manufacturing systems - Oleghe, Omogbai; Salonitis, Konstantinos (Emerald, 2018)
Purpose This study aims to seek to advance a system dynamics-discrete event hybrid simulation modelling concept useful for taking improvement decisions where one needs to consider the interactions between human factors and process flow elements in lean manufacturing systems. Design/methodology/approach A unique approach is taken to hybrid simulation modelling where the whole problem situation is first conceptualized using a causal loop diagram and stock and flow diagram, before transmitting to a hybrid simulation model. The concept is intended to simplify the simulation modelling process and make the concept pliable for use in various types of lean manufacturing problem situations. Findings The hybrid simulation modelling concept was applied to a lean manufacturing case where quality performance was sporadic mainly because of production pressures. The hybrid modelling concept revealed a solution that advanced full compliance with lean and one that required changes in job scheduling policies to promote both continuous improvement and throughput increases. Research limitations/implications Because non-tangible aspects of lean were objectively assessed using the hybrid modelling concept, the study is an advancement towards establishing a credible link between human resource aspects of lean and the performance of an organization. Practical implications The applied hybrid model enabled managers in the plant navigate the trade-off decision they often face when choosing to advance production output ahead of continuous improvement practices. Originality/value System dynamics-discrete event hybrid simulation modelling is a rarity in lean manufacturing systems.
Keywords: Discrete event simulation; System dynamics; Hybrid simulation modeling; Lean manufacturing system